The Pre-Enrollment Medical Student Data Predictios of Pre-Clinic Failure - Piyawan Chiengkriwate; Waranya Sripichian; Sunisa Musem (Journal of Health Science and Medical Research (JHSMR), 2017)
Objective: To identify potential pre-enrollment predictors of undergraduate medical students failure in pre-clinic class. Material and Method: A retrospective descriptive analytic study, medical students who had admitted in 2008-2012 to the Prince of Songkla University. The pre-enrollment data base was used to identify students background, high school Grade Point Average (GPA), Ordinary National Education Test (O-NET) score, and family background. The entry pathway and academic performance in the pre-clinic class were also collected and entered into analytic studies by using p-value<0.050 for each significant variable. Results: Nine hundred and fifty six medical students were enrolled, 418 (43.7%) was male, 274 (28.7%) had entered via the Collaborative Project to Increase Production of Rural Doctor (CPIRD) entry pathway, and 419 (43.8) had graduated from a high school in Songkhla province. Thirty nine (4.1%) students had failed in pre-clinic course. Comparing in achievement with the failure group revealed significant differences in GPA median (interquartile range) [3.8 (3.7, 3.9) vs 3.7 (3.5, 3.8)] and O-NET score [60 (51.4, 69.0) vs 53 (43.8, 60.0)], and proportion of CPIRD entry pathway (27.4% vs 59.0%) (p-value<0.001). However univariate conditional logistic regression analysis regression showed that the 10 (1%) with absent parent [odds ratio (OR)=42, 95% confidence interval (95% CI)=11.3 to 156 p-value<0.001), GPA less than 3.5 (OR=5.14, 95% CI=2.47 to 10.69, p-value<0.001), and O-NET score less than 50 compare with at least 60 (OR=4.34, 95% CI=1.81 to 10.40, p-value=0.001) were associated with pre-clinic failure. Conclusion: The GPA and O-NET scores, CPIRD entry pathway and absent parent were identified as significant pre-enrollment predictors of pre-clinic failure.